Pastoral dairy marketing and household wealth interactions and their implications for calves and humans in Ethiopia - Holden, S.J.; Coppock, D. Layne; Assefa, M. (1991)
Examines some interactions of market access and family wealth on household milk allocation for calves and people. Evaluates implications in terms of mortality and morbidity rates of nursing calves and the composition and nutritional value of human diets. Presents surveys of pastoral households in a semi-nomadic Boran community, in Ethiopia during 1987-1988 which were used to test the hypothesis that poorer families living closest to a market town would be most affected by the enhanced opportunity to sell dairy products, which would intensify competetion between people and calves for milk and have negative implications for calf management. Across all families the average rate of milk offtake per cow was 41+2.5 percent (x+ ISE; N=45 families with an average of 5.2 cows documented for each). Significant main effects are shown in Table I and illustrate that: 1. poorer families reported a high rate of milk offtake, 2. the higher-producing cows were reportedly milked intensively, and 3. milk offtake gradually increased over all wealth strata as distance to market decreased.